Vozes sociais em diálogo: uma análise bakhtiniana dos diários de leituras produzidos por alunos do ensino médio - Lima, Rhena Raize Peixoto de (2013)
The work aims to analyze high school students utterances, in reading diary discursive genre, starting from the language concept proposed by the Bakhtin Circle. The genre in question has peculiar characteristics which justify its choice for this work, especially with regard to subjectivity marks, that reveal, through the ideological clash, positions on various issues. From the utterances selected for the corpus, categories were created, during the research, according to the guidelines of Guba and Lincoln (2006), Mazzotti and Gewandsznajder (1998) and Amorim (2002), for whom the research in human sciences cannot be based on pre-established categories. We consider diary as a discursive genre (BAKHTIN, 2010a), which carries the characteristics of composition, style and content. Other concepts of the Circle, concerning to utterance, dialogical relations, social voices, responsiveness and exotopy also formed the basis for the study. Moreover, during the analysis of the utterances that compose the corpus of research, we used the concepts of discursive polemics (BAKHTIN, 2010b) and Framework (2010a). At the end of the research, we realized that the assessment situation of students, the fact that they are in an institution whose policy follows national documents, based on diversity and plurality, and live together in a classroom space where there are differences of social class, age, and finally, different realities, were not sufficient factors for this diversity be well accepted in their positions. Thus, their utterances bring voices that demonstrated a difficulty in accepting others that are different from themselves. In view of this, we conclude that teachers need to be prepared to handle these discourses, creating strategies for mediating these dissonant voices, with which must make contact every day at school